Synthesis of Cr-doped SrTiO3 photocatalyst and its application in visible-light-driven transformation of CO2 into CH4. (December 2015) - Bi, Yiqing; Ehsan, Muhammad Fahad; Huang, Yan; Jin, Jiarui; He, Tao
Graphical abstract: Cr-doped SrTiO3 synthesized by ultrasonic chemical route can photoreduce CO2 into CH4 under visible-light irradiation with a yield of 8.8 μmol g −1 . Highlights: Cr-doped SrTiO3 is successfully synthesized by a facile ultrasonic chemical route. Cr-doped SrTiO3 exhibits a large specific surface area and visible-light response. CO2 is photoreduced into CH4 over Cr-doped SrTiO3 under visible-light irradiation. Cr-doped SrTiO3 shows good stability against photoirradiation. Abstract: Visible-light-driven Cr-doped SrTiO3 was synthesized through ultrasonic chemical method. Its specific surface area is 54.3 m 2  g –1 due to the relatively small particle size. X-ray diffraction pattern and X-ray photoelectron spectra confirmed the crystal structure and Sr substitution. UV–vis absorption spectra indicated that the Cr doping can lead to visible-light absorption. In addition, the oxygen vacancy in Cr-doped SrTiO3 also showed visible-light absorption. The obtained Cr-doped SrTiO3 was used to photocatalytically reduce CO2 into CH4 with a yield of 8.8 μmol g –1 after 10-h reaction. Moreover, the Cr-doped SrTiO3 exhibited good photostability.